2023
DOI: 10.1007/s11655-023-3693-1
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activity of Diosgenin and Its Molecular Mechanism

Abstract: Diosgenin, a steroidal sapogenin, obtained from Trigonella foenum-graecum, Dioscorea , and Rhizoma polgonati , has shown high potential and interest in the treatment of various cancers such as oral squamous cell carcinoma, laryngeal cancer, esophageal cancer, liver cancer, gastric cancer, lung cancer, cervical cancer, prostate cancer, glioma, and leukemia. This article aims to provide an overview of the in vivo, in vitro , and clinical studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 119 publications
0
9
0
Order By: Relevance
“…Of the various sapogenins, diosgenin could be prized because of its suitable structure and abundant source capable of meeting industrial scale demand [28]. Recently, many studies have found that diosgenin itself has therapeutic effects on a variety of diseases, such as cancers [29], inflammatory and metabolic diseases [30], diabetes [5], hypolipidemia [31], atherosclerosis [32] and cardiac diseases [33]. With the increasing use of diosgenin in the pharmaceutical industry and therapeutic treatment, the demand for diosgenin is increasing rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…Of the various sapogenins, diosgenin could be prized because of its suitable structure and abundant source capable of meeting industrial scale demand [28]. Recently, many studies have found that diosgenin itself has therapeutic effects on a variety of diseases, such as cancers [29], inflammatory and metabolic diseases [30], diabetes [5], hypolipidemia [31], atherosclerosis [32] and cardiac diseases [33]. With the increasing use of diosgenin in the pharmaceutical industry and therapeutic treatment, the demand for diosgenin is increasing rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…This modulation involves the manipulation of EMT-associated proteins like transforming growth factor β1, E-cadherin, and vimentin. Diosgenin also triggers apoptosis in A549 cells through its impact on proteins within the MAPK signal pathway, including caspase 8, 9, and 3 [ 83 ]. Diosgenin downregulates the MAPK, NF-κB, and Akt signaling pathways by inhibiting the phosphorylation of NF-κB/p65, JNK, IKK-β, Akt, and ERK, resulting in its anti-tumor effect.…”
Section: Secondary Metabolites From Solanaceaementioning
confidence: 99%
“…Diosgenin, a major sapogenin found in fenugreek seed, has shown high potential and interest in the treatment of various cancers such as GC [211]. Previous studies have shown that diosgenin has effects that inhibit mesoderm posterior 1 (MESP1) expression, leading to suppressed proliferation of GC cells via inducing alternative reading frame (ARF) expression.…”
Section: Fenugreekmentioning
confidence: 99%